Higher Education Pathways South African Undegraduate Education and the Public Good - Ashwin, Paul; Case, Jennifer M (African Higher Education Dynamics Series, 2018)
"In what ways does access to undergraduate education have a transformative impact on people and societies? What conditions are required for this impact to occur? What are the pathways from an undergraduate education to the public good, including inclusive economic development? These questions have particular resonance in the South African higher education context, which is attempting to tackle the challenges of widening access and improving completion rates in in a system in which the segregations of the apartheid years are still apparent. Higher education is recognised in core legislation as having a distinctive and crucial role in building post-apartheid society. Undergraduate education is seen as central to addressing skills shortages in South Africa and is also seen to yield significant social returns, including a consistent positive impact on societal institutions and the development of a range of capabilities that have public, as well as private, benefits. However, the precise extent and nature of these impacts remain unclear, particularly in light of contemporary global, social and economic challenges. This book offers comprehensive contemporary evidence that allows for a fresh engagement with these pressing issues."